THE ROLE OF THE PHONICS METHOD IN STIMULATING READING AND LANGUAGE SKILLS IN CHILDREN AGED 3–6 YEARS WITH SPEECH DELAY - Firsiyanti, Aty; Rayhani, Salsabila (UNG, 2025)
Phonics is a method of teaching reading and speech that emphasizes the systematic relationship between letters and sounds (phonemes). This study systematically reviews effective phonics strategies for children aged 3–6 years with speech delays, while also identifying success factors and formulating practical recommendations. The novelty of this study lies in its exclusive focus on early childhood with speech delays and its multidimensional perspective, which integrates technology, clinical profiling, and the mapping of seven key success factors. The primary contribution is the development of evidence-based, practice-oriented recommendations for both speech therapy professionals and family caregivers, thereby extending the applicability of phonics interventions beyond previous reviews. The research employed a Systematic Literature Review (SLR) guided by PRISMA, ensuring methodological rigor. From 660 publications identified through Google Scholar (2020–2025), 21 studies were retained using eight quality criteria and analyzed narratively. Although Google Scholar served as the main database, it indexes reputable journals listed in Scopus, PubMed, and Web of Science, thus ensuring diversity and reliability. Findings indicate that phonics interventions are effective for children with Autism Spectrum Disorder (ASD), Developmental Language Disorder (DLD), hearing impairments, and bilingual contexts. Success depends on early and accurate diagnosis, intensive and structured sessions, adaptive digital technology, and sustained professional support. However, further field trials in Indonesia are recommended to evaluate contextual applicability, especially concerning standardized diagnostic tools, personalized interventions, digital learning integration, and active parental involvement in therapy.